Staged Analysis of RC Frame Retrofitted with Steel Braces in Low and Medium-rise Buildings. (2017) - Sukrawa, Made
Abstract: The emerging concept of sustainable construction has lead researchers and practicing engineers to preserve and strengthen existing structures to minimized use of materials and energy associated with it. As a result, many retrofitting techniques for RC frame structures has been proposed and applied as opposed to reconstruction. Among the techniques to increase the seismic load carrying capacity of existing structures, the use of steel braces is very popular and relatively easy to work on. This paper try to consider construction and loading stages in the analysis of earthquake responses of existing RC frame retrofitted with steel braces for low and medium-rise buildings. For that purposes, RC frames of 3, 5, 8, and 10 story typical office buildings were designed consisting of four 3-bays frames in each direction. The chevron A and X-shaped braces were added to the middle bay of the exterior frames to minimized functional changes of the building. Analyses of 3-D models show that the earthquake response of RC frames with A and X steel braces are significantly stiffer and stronger than the original bare frames. The reinforcement requirement in the frames also reduced significantly with the addition of braces. Compared to conventional analysis, staged analysis using cracked section produce larger deformation and forces on the frames, and accordingly, should be used in the analysis to have more accurate result and safer design.